History of the Colombian armed conflict and paramilitarism narrated by students: silence and misrepresentation surrounding a controversial history (Tempo e Argumento, 2021)
By means of content analysis of historical narratives written by 86 high school students assigned to 3 public institutions in the city of Bogotá, this study addresses their conceptions of the history of the Colombian armed conflict and the participation of paramilitary groups in this conflict. To do this, the article is structured around 3 exposition axes. On the first axis, the study analyzes contextual elements aimed at understanding the armed conflict and paramilitarism as historical phenomena, the current state of research on recent history teaching in Colombia, and the place that conflict and paramilitarism occupy as topics to be taught in the official social sciences curriculum. On the second axis, the methodology used to carry out the research is detailed, emphasizing the sample’s characteristics and the information analysis plan. On the third axis, the findings obtained are socialized, highlighting, on the one hand, the interpretive and explanatory issues that students face at the time of accounting for the various variables, agents and historical processes determining the armed conflict, and, on the other hand, the widespread ignorance about the nature and actions of paramilitarism, which translate into the reproduction of a series of silences and historical misrepresentations.Keywords: Armed conflict. Paramilitarism. Student conceptions. Recent history teaching. Colombia.